Fragile X mental retardation protein (FMRP) interacting proteins exhibit different expression patterns during development. Issue 42 (11th February 2015) - Bonaccorso, C.M.; Spatuzza, M.; Di Marco, B.; Gloria, A.; Barrancotto, G.; Cupo, A.; Musumeci, S.A.; D'Antoni, S.; Bardoni, B.; Catania, M.V.
Abstract: Fragile X syndrome is caused by the lack of expression of fragile X mental retardation protein (FMRP), an RNA‐binding protein involved in mRNA transport and translation. FMRP is a component of mRNA ribonucleoprotein complexes and it can interact with a range of proteins either directly or indirectly, as demonstrated by two‐hybrid selection and co‐immunoprecipitation, respectively. Most of FMRP‐interacting proteins are RNA‐binding proteins such as FXR1P, FXR2P and 82‐FIP. Interestingly, FMRP can also interact directly with the cytoplasmic proteins CYFIP1 and CYFIP2, which do not bind RNA and link FMRP to the RhoGTPase pathway. The interaction with these different proteins may modulate the functions of FMRP by influencing its affinity to RNA and by affecting the FMRP ability of cytoskeleton remodeling through Rho/Rac GTPases. To better define the relationship of FMRP with its interacting proteins during brain development, we have analyzed the expression pattern of FMRP and its interacting proteins in the cortex, striatum, hippocampus and cerebellum at different ages in wild type (WT) mice. FMRP and FXR2P were strongly expressed during the first week and gradually decreased thereafter, more rapidly in the cerebellum than in the cortex. FXR1P was also expressed early and showed a reduction at later stages of development with a similar developmental pattern in these two regions. CYFIP1 was expressed at all ages and peaked in the third post‐natal week. In contrast, CYFIP2 and 82‐FIP (only in forebrain regions) were moderately expressed at P3 and gradually increased after P7. In general, the expression pattern of each protein was similar in the regions examined, except for 82‐FIP, which exhibited a strong expression at P3 and low levels at later developmental stages in the cerebellum. Our data indicate that FMRP and its interacting proteins have distinct developmental patterns of expression and suggest that FMRP may be preferentially associated to certain proteins in early and late developmental periods. In particular, the RNA‐binding and cytoskeleton remodeling functions of FMRP may be differently modulated during development.